Studi Tentang Rasialisme Dalam Fikn The Green Mile (Jurnal Ilmu-Ilmu Sejarah, Budaya Dan Sosial ( LENTERA ), 2009)
This research is about raciahsm and the forms of Blacks stereotype in America, and its relation to the films of The Green MUe.Racialism in the films The Green Mile Blacks were represented in theform of negative stereotype namely, stupidity, laziness, murder, andsuperstition. This research uses an interdisciplinary approach by usinghistory, sociology and culture perspective. Racialism in America has beena dilemma for Blacks, because of racial prejudice, discrimination,segregation and unjust treatment of them by Whites. Many blacks haveproblems or difficulties in the aspect of their lives. For example they donot have equality in education, employment, and law protection. Blacksin America are regarded as inferior while whites are regarded as superior.The result of this research indicated that The Blacks character in the fiknThe Green Mile is typical of the type of stereotype that appeared in slaveryera. In the film The Green Mile Blacks characters were also showed as akind of caricature of Tom, Sambo, Coons, and Bucks. In the films TheGreen Mile, gave audience not only entertainment but also informationabout the black experience in America.Keywords: Racialism, inferiority, superiority, discrimination, stereotyp